The AI Co-pilot: Navigating Market Turbulence and Charting a Course for Sustainable Advantage - Simon Suwanzy Dzreke (Sultan Publisher, 2025)
This study addresses the gap in frameworks for effective human-AI collaboration in strategic decision-making during turbulent market conditions. Using a mixed-methods approach (longitudinal case studies in manufacturing, finance, and logistics; large-scale executive surveys; computational simulations), we empirically evaluate the